2019
DOI: 10.1002/glia.23754
|View full text |Cite
|
Sign up to set email alerts
|

Bmal1‐deficiency affects glial synaptic coverage of the hippocampal mossy fiber synapse and the actin cytoskeleton in astrocytes

Abstract: Bmal1 is an essential component of the molecular clockwork, which drives circadian rhythms in cell function. In Bmal1‐deficient (Bmal1−/−) mice, chronodisruption is associated with cognitive deficits and progressive brain pathology including astrocytosis indicated by increased expression of glial fibrillary acidic protein (GFAP). However, relatively little is known about the impact of Bmal1‐deficiency on astrocyte morphology prior to astrocytosis. Therefore, in this study we analysed astrocyte morphology in yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 73 publications
(103 reference statements)
1
23
0
Order By: Relevance
“…We have shown that adult neurogenesis is affected in BMAL1-deficient mice [ 59 , 131 , 132 ]. Moreover, the fine astrocytic processes ensheathing the hippocampal mossy fibre synapse and the astrocyte actin cytoskeleton are affected in BMAL1-deficient mice [ 133 ], indicating that the molecular clockwork modulates astrocyte-neuron interaction at the structural level of the tripartite synapse. Consistently, both neurons and astrocytes show time-of-day-dependent structural and functional changes in CA1, while pyramidal neurons change the surface expression of NMDA receptors, and astrocytes change the proximity to synapses [ 80 ].…”
Section: The Role Of Light and The Circadian Clock For Rhythmic Brain...mentioning
confidence: 99%
“…We have shown that adult neurogenesis is affected in BMAL1-deficient mice [ 59 , 131 , 132 ]. Moreover, the fine astrocytic processes ensheathing the hippocampal mossy fibre synapse and the astrocyte actin cytoskeleton are affected in BMAL1-deficient mice [ 133 ], indicating that the molecular clockwork modulates astrocyte-neuron interaction at the structural level of the tripartite synapse. Consistently, both neurons and astrocytes show time-of-day-dependent structural and functional changes in CA1, while pyramidal neurons change the surface expression of NMDA receptors, and astrocytes change the proximity to synapses [ 80 ].…”
Section: The Role Of Light and The Circadian Clock For Rhythmic Brain...mentioning
confidence: 99%
“…Accumulated levels of PER and CRY within the cytoplasm feed back into the nucleus, displacing the CLOCK and BMAL1 heterodimer and consequently disrupting their own transcription ( 11 ). This transcriptional machinery regulates cytoskeletal factors ( 12 ), cell cycle ( 13 ), and metabolism ( 14 ) in numerous cell populations. OPCs proliferate on a circadian cycle ( 4 ) and sleep deprivation negatively impacts OPC proliferation and differentiation ( 15 ).…”
Section: Main Textmentioning
confidence: 99%
“…In line with this hypothesis, astrocytes of Ophn1 -KO mice are less ramified and show altered migration and glial scar formation [ 326 ]. Moreover, mice deficient for ARNTL (aryl hydrocarbon receptor nuclear translocator like, also known as Bmal1), an essential component of the molecular clockwork driving circadian rhythms, showed severe cognitive deficits, associated with a reduction of perisynaptic astrocytic processes covering hippocampal mossy fiber synapses, which is probably due to a reduction of RHOA activity in Arntl -deficient astrocytes [ 327 ].…”
Section: Cytoskeleton In Non-neuronal Cells and Idmentioning
confidence: 99%